New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species - Zhao, Yang; Tian, Yanlin; Liu, Zhiqi (Zootaxa, 2017)
A new species of the genus Wesmaelius is described from China: Wesmaelius dissectus sp. nov., which was found in Sichuan province. Wesmaelius ravus (Withycombe, 1923) was recorded in China for the first time in Hubei province and Inner Mongolia. The Wesmaelius helanensis Tian & Liu, 2011 is redescribed, with the first discovery of female in China. Updated keys to the adult males and females of the Wesmaelius from China are also provided.